PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS IV MATERI BERMAIN MUSIK SEDERHANA DALAM MENGIRINGI LAGU DAERAH MELALUI MODEL PEMBELAJARAN LANGSUNG DI MIN 2 PANDEGLANG - Ma’rifah, Lilis Nurul; Yajid, Yajid; Kosim, Nandang; Zaelani Rahman, Elan (Staisman Press, 2022)
Low activity and learning outcomes are caused by students not understanding the subject matter, learning conducted by teachers is less interesting, students are less active and less enthusiastic when participating in learning the art of music. To increase the activity and student learning outcomes, the researchers used a learning model that made it possible to achieve these goals, namely the direct learning model. This classroom action research was conducted in 2 cycles. Each cycle consists of 2 meetings where cycle evaluation is carried out at the end of the cycle. Assessment of student learning outcomes is carried out through assessing the performance of students playing simple music in accompaniment to folk songs in groups. The subjects of this study were students of class IV MIN 2 Pandeglang in semester II. The type of data taken is quantitative and qualitative data. Data collection techniques are tests and nontes. Indicators of success in this study are the percentage of student learning activity of at least 75%, student completeness of at least 75%, and teacher performance of at least B (70). Research that has been done in cycle 1 shows that student learning activity reaches 73.4%. Students who have completed learning are 25 students or 65%, students who have not completed learning are 15 students or 35%, and the average learning result reaches 73.13. The teacher's ability score in cycle 1 reached 78.83 with AB criteria. Based on the results of cycle 1 research, it is necessary to continue action research in cycle 2 to increase student activity and learning outcomes. Research cycle 2 obtained the results of student learning activities 81.5%. Students who complete the study are 37 students or 92.5%, students who do not complete are 3 students or 7.5%, and the class average is 80.4. The value of the teacher's ability in cycle 2 reached 96.71 with criterion A. The research that has been done shows that direct learning can be applied to learning material for playing simple music in accompaniment to folk songs. Based on the results of the study it can be concluded that the direct learning model can improve learning activities, student learning outcomes, and teacher performance in learning the art of music playing simple music in accompaniment to folk songs.